A qualitative analysis of perceptions of orthodontists in Concepción about removable orthodontic appliances - Matthews, Francisca (Journal of Oral Research, 2019)
To determine the utilization, attitudes and perceptions about removable orthodontic appliances (ROA) among a sample of Chilean orthodontists. Materials and methods: Data collection was performed using semi-structured interviews with 10 orthodontists from diverse professional backgrounds. The analysis was performed using the “Grounded Theory” methodology, using Atlas.ti v.6.0.15. Results: We interviewed four men and six women (31 to 75 years old), with 7 to 53 years of experience as dentists, and 1 to 10 years of experience as orthodontists. All orthodontists have experience in private practice, five in public service, and one in a military institution. Onehundred and thirty-three codes were grouped into seven categories identified as follows: perception of orthodontists, control over treatment, ROA characteristics, ROA indications and contraindications, patients’ attitude to ROA, selection of treatment, and ROA utilization.